Patent Protection for Artificial Intelligence: Contemporary Legal Challenges and Regulatory Perspectives - Sarmad Dalaf Hanoosh; Ahmed Abed; Souria Mazouz; Aqeel Sarhan Fayyadh; Neamah Rashid Salih (PT. Islamic Research Publiser, 2026)
The rapid advancement of artificial intelligence (AI) technologies has created significant legal challenges within the framework of intellectual property law, particularly regarding the adequacy of patent protection for AI applications. Traditional patent systems were originally designed to regulate inventions created by human inventors, which has raised uncertainty concerning the legal status of AI-related innovations and their compliance with patentability requirements. This research examines the extent to which existing patent provisions can provide effective legal protection for artificial intelligence applications under Iraqi law in comparison with selected comparative legal systems. The study seeks to answer several questions, including whether AI applications may qualify as patentable inventions, whether traditional patent conditions remain sufficient to address AI technologies, and what legal implications arise from granting patent protection to such applications. The research adopts a doctrinal legal methodology based on descriptive, analytical, and comparative approaches. It relies on primary legal sources, including legislation, judicial decisions, and international agreements, as well as secondary academic sources on artificial intelligence and patent law. The study finds that although traditional patent rules face challenges in accommodating AI technologies, patent law remains one of the most appropriate legal mechanisms for protecting AI applications, particularly when they satisfy the requirements of novelty, inventive step, and industrial applicability. The research further concludes that current Iraqi patent legislation requires legislative reform to address the unique characteristics of AI technologies and to establish more flexible legal standards capable of responding to rapid technological development. The academic contribution of this study lies in clarifying the relationship between AI applications and patent protection and in proposing legal approaches that balance technological innovation with effective intellectual property protection.